Shielding evaluation for solar particle events using MCNPX, PHITS and OLTARIS codes. (January 2015) - Aghara, S.K.; Sriprisan, S.I.; Singleterry, R.C.; Sato, T.
Abstract: Detailed analyses of Solar Particle Events (SPE) were performed to calculate primary and secondary particle spectra behind aluminum, at various thicknesses in water. The simulations were based on Monte Carlo (MC) radiation transport codes, MCNPX 2.7.0 and PHITS 2.64, and the space radiation analysis website called OLTARIS (On-Line Tool for the Assessment of Radiation in Space) version 3.4 (uses deterministic code, HZETRN, for transport). The study is set to investigate the impact of SPEs spectra transporting through 10 or 20 g/cm 2 Al shield followed by 30 g/cm 2 of water slab. Four historical SPE events were selected and used as input source spectra particle differential spectra for protons, neutrons, and photons are presented. The total particle fluence as a function of depth is presented. In addition to particle flux, the dose and dose equivalent values are calculated and compared between the codes and with the other published results. Overall, the particle fluence spectra from all three codes show good agreement with the MC codes showing closer agreement compared to the OLTARIS results. The neutron particle fluence from OLTARIS is lower than the results from MC codes at lower energies ( E < 100 MeV ). Based on mean square difference analysis the results from MCNPX and PHITS agree better for fluence, dose and dose equivalent when compared to OLTARIS results.